A conceptual morphology of environmental scepticism. Issue 3 (2nd September 2019) - Harding, Eloise
ABSTRACT: As environmental and ecological discourses have gained increasing attention in the political arena, those opposed to such discourses have fought for political ground. Drawing elements from classical conservatism, economic liberalism and right-wing libertarianism, environmental scepticism has coalesced around a conceptual core of deep anthropocentrism, Prometheanism, a suspicious framing of environmentalism and a highly specific conception of science. While environmental scepticism lacks a wider social agenda, its conceptual core is sufficient for it to be considered a thin ideology. This article explores the conceptual clusters that make environmental scepticism distinctive.